E-store loyalty: Longitudinal comparison of website usefulness and satisfaction - Pee, Loo Geok (2018)
Customer loyalty is vital to the survival of online stores. Many cross-sectional studies have shown that e-store loyalty is strongly affected by perceived website usefulness (PU) and satisfaction with a purchase experience. By its very nature, loyalty develops cumulatively over multiple purchases. Yet, our understanding of how longitudinal changes in PU and satisfaction influence the development of (i.e., change in) loyalty remains limited. Drawing upon the information-processing perspective and experiential perspective of customer evaluation, this study shows that PU has a stronger effect on loyalty in the first purchase. In subsequent purchases, PU changes less (i.e., is more stable) than satisfaction. Furthermore, change in satisfaction has a stronger effect in the development of (i.e., change in) loyalty. This study extends research by clarifying the differential longitudinal changes and effects of two important antecedents of e-store loyalty. For practitioners, the findings suggest a longitudinal approach to initiate and nurture e-store loyalty that focuses on clarifying the usefulness of website to new customers, while increasing the satisfaction of returning customers.